Holocene environmental reconstruction at Lough Doo, Co. Mayo, Ireland: pollen, chemistry and palaeomagnetics - Michael O extquotesingleConnell (PANGAEA, 2018)
Multiproxy analyses carried out on a 3-m core from L. Doo, a 6.3 ha lake, east of Attymass, Co. Mayo in the early 1980s. Pollen counts (M O extquotesingleConnell & FJG Mitchell), 14C dates (Groningen 14C lab) and geochemical data (TJ Doherty & DA Murray) provided. Natural remanent magnetisation (NRM) results by PW Readman discussed in main publication (O extquotesingleConnell et. al. 1987 in JQS 2:149-164). Age/depth model constructed using clam v. 2.2 (details are provided)